Grupos interativos de aprendizagem como prática educativa para o ensino de conceitos físicos da cinemática - Silva, Ronaldo Nogueira (2019)
The information society, in which we are inserted, has a permanent community of consultation, consultation and sharing of knowledge and knowledge with an interaction in large part through Digital Communicative and Information Technologies (TDCI) and the coexistence between the various groups or social networks . The teaching of practical skills and educational practices that make it possible to carry out teaching tasks as of today is as effective as the current results. part of the students. The research has as its theme: interactive learning groups as an educational practice for teaching kinematics, based on dialogic learning. The main one was a perspective of students' learning, an understanding of concepts of kinematics through the principles of practice. As a specific objective, to promote the teaching of Physics through the work in group of students and to provide the best practices in the learning and the coexistence between students. The research was conducted in a state public school in the city of Cascavel - CE had a direct participation of 73 students of the previous series of High School. This study is characterized as a research of qualitative-educational approach, in which were adopted the deductive and inductive methods, divided into two phases. The first phase, bibliographical, based on some theoretical assumptions, including Lev Vygotsky, Paulo Freire, Jürgen Habermas (Dialogical Learning) and a research INCLUD-ED(2012); in the second phase, conducted a field research, held in the school itself. As for development, the study was constructed in two stages. First type of expository activities and proposals resolution, in a total of 6 hours / class, divided in three meetings; and in a second moment, with didactic didactics applying an educational practice Interactive Group in the Experimental Class in a total of 4 hours / classes divided in two meetings, generation in the classroom. The first, the first and the second grade were the diagnostic tests that consisted of a socioeconomic survey and a closed questionnaire, a pretest level, with no beginning and a posttest level at the end, using 2 hours / class. This study was tabulates, study and representations for the preparation of research and later. You can still use this study, but it is also interesting to use related topics such as interacting with classroom activities, helping to raise interest and improve student performance in the classroom. the students may come to increase their coexistence in the educational lecture of the propitiate acceleration of learning to some, beyond values and feelings to the friendship and solidarity.